2012
DOI: 10.1021/es301430u
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Protection, Integrated Management and Infrastructure are Vital for Improving Water Quality in Africa

Abstract: A ccess to safe water and sanitation is an important component of the Millennium Development Goals (MDGs). It was expected that 86% of the developing world would have gained access to safe drinking water by 2015. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…For example, Kenya supplies 25% of Europe's cut flowers (http://www.economist.com/node/10657231). Consequently, the greenhouses for rose planting have become a major source of water pollution . In Lake Naivasha, Kenya, we found that the biodiversity has been shrinking in recent years.…”
Section: Sources Of Water Pollutionmentioning
confidence: 88%
See 2 more Smart Citations
“…For example, Kenya supplies 25% of Europe's cut flowers (http://www.economist.com/node/10657231). Consequently, the greenhouses for rose planting have become a major source of water pollution . In Lake Naivasha, Kenya, we found that the biodiversity has been shrinking in recent years.…”
Section: Sources Of Water Pollutionmentioning
confidence: 88%
“…The lack of power supply also hinders water and wastewater treatment to a great extent in Africa . We found that many treatment plants cannot operate properly due to unreliable power supply system.…”
Section: Challenges For Water and Wastewater Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Successful waste treatment technologies should be sustainable, support periurban primary industry such as agriculture, prevent exploitation of water reserves and other resources, and enhance the quality of life of the community (Wang et al, 2012). Wastewater treatment must be biologically/mechanically rigorous, ecologically sound and environmentally friendly (Golueke and Oswald, 1963;Oswald, 1991Oswald, , 1995 and the WWTW solid, able to withstand the elements and require minimal maintenance over an extended period of time (Wallis et al, 2008;González et al, 2012).…”
Section: Iaps As a Bioprocess Technology For Wastewater Treatmentmentioning
confidence: 99%
“…High turbidity, which decreases the quality of drinking water, is one of the major problems of sources of drinking water in Africa. For instance, in Nairobi, the turbidity of raw water can be 3 NTU in the dry season, and it may reach to 5000 NTU during the rainy season [17,18]. It is reported that the turbidity of Blue Nile and River Nile may reach 7,275 NTU and 6,575 NTU, respectively [11].…”
Section: Introductionmentioning
confidence: 99%